Sustainable Crop Production - Recent Advances 2022
DOI: 10.5772/intechopen.102595
|View full text |Cite
|
Sign up to set email alerts
|

Toward the Recent Advances in Nutrient Use Efficiency (NUE): Strategies to Improve Phosphorus Availability to Plants

Abstract: Achieving high nutrient use efficiency (NUE) and high crop productivity has become a challenge with increased global demand for food, depletion of natural resources, and deterioration of environmental conditions. Higher NUE by plants could reduce fertilizer input costs, decrease the rate of nutrient losses, and enhance crop yields. Nitrogen and Phosphorus are the most limiting nutrients for crop production in many of the world’s agricultural areas, and their efficient use is important for the economic sustaina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 100 publications
0
2
0
Order By: Relevance
“…In addition to crop‐rotation strategies, adjusting fertilization methods and rates to better suit specific crops as well as using targeted crop species that are more efficient in nutrient use can also increase yields (Ebbisa, 2022; Guo et al., 2020; Pan et al., 2022). Improving such local to regional farmland management strategies could lead to a reduced need for fertilizers and improve both the quality of soil and water resources as well as enhancing future food production at local‐global scales (Billen et al., 2021; Chang et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to crop‐rotation strategies, adjusting fertilization methods and rates to better suit specific crops as well as using targeted crop species that are more efficient in nutrient use can also increase yields (Ebbisa, 2022; Guo et al., 2020; Pan et al., 2022). Improving such local to regional farmland management strategies could lead to a reduced need for fertilizers and improve both the quality of soil and water resources as well as enhancing future food production at local‐global scales (Billen et al., 2021; Chang et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Improvements in NUE under aerobic rice systems and other non-N 2 -fixing crops are required to fulfill the future food requirements of the projected inflation in the population via improved and modified N-use efficient varieties along with other crops, irrigation, and fertilizer management practices ( Mboyerwa et al, 2021 ). Management practices that focus on improving plant N uptake and NUE involve irrigation methods, fertilizer input management, crop variety management in terms of water and NUE, plant N uptake management, use of controlled-release N fertilizers, use of NIs and urease inhibitors for synthetic N fertilizers, and other agronomic integrative crop management approaches ( Pan et al, 2017 ; Gweyi-Onyango et al, 2021 ; Williams et al, 2021 ; Ebbisa, 2022 ; Ma X. et al, 2022 ). Several studies regarding NUE have demonstrated that it is majorly associated with the type and method of fertilizer inputs, irrigation methods, availability of soil N, and plant N uptake ( Ye et al, 2013 ; Rawal et al, 2022 ).…”
Section: Toward Eco-efficient N Managementmentioning
confidence: 99%